A study of the perceptions of teachers towards a holistic approach in teaching in CBSE board schools in the context of NEP 2020 at the foundational and preparatory stages - Rajwade, Priya; Bansal, Alka (The Scientific Temper, 2025)
This study examines teachers' perceptions towards adopting a holistic approach to teaching at the foundational and preparatory stages within CBSE schools, in alignment with the National Education Policy (NEP) 2020. NEP 2020 marks a pivotal shift in India's educational framework, emphasizing the holistic development of students through a focus on intellectual, emotional, physical, social, and moral growth. This research investigates teachers' awareness, preparedness, and willingness to implement this pedagogical shift alongside the challenges they foresee in its adoption. Using a mixed-methods approach, the study involved 80 CBSE teachers from Mumbai, employing survey questionnaires and structured interviews for data collection. Quantitative analysis revealed that 77.5% of the participants demonstrated substantial awareness of the NEP’s goals, with teachers expressing positive perceptions toward holistic education. However, qualitative findings identified key challenges, including limited resources, insufficient training, parental interference, and the need for curriculum alignment. Teachers acknowledged the transformative potential of holistic teaching in fostering well-rounded student development and cited innovative classroom practices as examples. Statistical analysis, including a one-tailed t-test, highlighted significant differences in teacher preparedness between foundational and preparatory stages. The findings underscore the need for targeted training programs, curriculum redesign, and systemic support to implement effectively. The study concludes that while teachers are optimistic and willing to embrace change, addressing systemic barriers is critical for achieving the NEP 2020’s vision. Recommendations include enhanced teacher engagement, capacity building, and resource allocation to ensure a sustainable shift towards holistic education.